Time evolution of copper-aluminum alloy laser-produced plasmas in vacuum. (November 2021) - Gao, Chunli; Min, Qi; Liu, Jinzhu; Hu, Susu; Du, Ying; Wu, Yanhong; Cao, Shiquan; Sun, Duixiong; Dong, Chenzhong; Su, Maogen
Highlights: The spectrum was obtained using spatio-temporal resolved spectroscopy technique. Plasma plume images were obtained using time-resolved transient imaging. Time evolutions of plasma parameters and were obtained. Abstract: Spectral and transient image measurements of the spatiotemporal evolution of laser-produced plasma of copper-aluminum alloy in vacuum and corresponding radiation hydrodynamics simulations are reported. The visible spectrum and time resolved plasma plume images were obtained for time delays from 10-100 ns at different positions near the target surface using space and time-resolved spectroscopy and time-resolved transient imaging. Using a program developed for multi-element laser-produced plasma simulation based on the radiation hydrodynamics model combined with experimental spectrum, ion/electron densities and plasma temperature as well as their time evolutions were obtained. The temporal and spatial distribution characteristics for Cu and Al ions in the plasma are clarified. These results will be helpful for understanding the dynamics of the different ions during expansion of multi-element laser-produced plasma and its applications.